The third gilmore girl ebook A memoir. - Bishop, Kelly (2024)
INSTANT NEW YORK TIMES BESTSELLER A Goodreads Choice Awards Winner "Come for the Gilmore Girls anecdotes, stay for the revealing truths about what it takes to build a lifelong career in and out of Hollywood" ( The A.V. Club ) in this candid and captivating memoir from award-winning and beloved actress Kelly Bishop, spanning her six decades in show business from A Chorus Line , Dirty Dancing , Gilmore Girls , and much more. Kelly Bishop's long, storied career has been defined by landmark achievements, from winning a Tony Award for her turn in the original Broadway cast of A Chorus Line to her memorable performance as Jennifer Grey's mother in Dirty Dancing . But it is probably her iconic role as matriarch Emily in the modern classic Gilmore Girls that cemented her legacy. Now, Bishop reflects on her remarkable life and looks towards the future with The Third Gilmore Girl . She shares some of her greatest stories and the life lessons she's learned on her journey. From her early transition from dance to drama, to marrying young to a compulsive gambler, to the losses and achievements she experienced—among them marching for women's rights and losing her second husband to cancer—Bishop offers a rich, genuine celebration of her life. Full of witty insights and featuring a special collection of personal and professional photographs, The Third Gilmore Girl is a warm, unapologetic, and spirited memoir from a woman who has left indelible impressions on her audiences for decades and has no plans on slowing down.